Unfavourable cardiovascular disease risk profiles in a cohort of Dutch and British haemophilia patients - Fransen van de Putte, Dietje E.; Fischer, Kathelijn; Makris, Michael; Tait, Campbell R.; Chowdary, Pratima; Collins, Peter W.; Meijer, Karina; Roosendaal, Goris; Schutgens, Roger E. G.; Mauser-Bunschoten, Eveline P. (Thrombosis and Haemostasis, 2013)
Cardiovascular disease (CVD) mortality is reported to be decreased in haemophilia patients, but reports on the prevalence of CVD risk factors are conflicting. A cross-sectional assessment of CVD risk profiles was performed in a large cohort of haemophilia patients. Baseline data on CVD risk factors of 709 Dutch and UK haemophilia patients aged ≥ 30 years were analysed and compared with the general age-matched male population. CVD risk profiles were assessed using the QRISK®2–2011 and SCORE algorithms. Although QRISK®2 was only validated in the UK, comparison with SCORE indicated similar properties of QRISK®2 in both Dutch and UK patients (correlation 0.86). Mean age was 49.8 years. Hypertension was more common in haemophilia patients than in the general population (49% vs. 40%), while the prevalences of obesity and hypercholesterolaemia were lower (15 vs. 20% and 44 vs. 68%, respectively), and those of diabetes and smoking were similar. The predicted 10-year QRISK®2 risk was significantly higher in haemophilia patients than in the general population (8.9 vs. 6.7%), indicating more unfavourable cardiovascular disease risk profiles. This increased risk became apparent after the age of 40 years. Our results indicate an increased prevalence of hypertension and overall more unfavourable CVD risk profiles in haemophilia patients compared with the general age-matched male population.
Keywords: Cardiovascular disease; haemophilia; hypertension; QRISK; risk profile